2016
DOI: 10.1159/000447360
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Artery Embolization: A Promising Technique in the Treatment of High-Risk Patients with Benign Prostatic Hyperplasia

Abstract: Introduction: Prostatic artery embolization (PAE) has recently started to be viewed as a promising technology that could be an alternative to different treatment options of benign prostatic hyperplasia (BPH), especially in high-risk patients. The aim of our study was to evaluate the efficacy and safety of PAE in BPH patients who are at high risk for surgery and/or anesthesia. Materials and Methods: Between June 2013 and February 2015, BPH patients >50 years with lower urinary tract symptoms (LUTS) refractory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…For BPH patients who are at high risk for surgery and/or anesthesia, prostatic artery embolization (PAE) may be a promising technique. No major complications were reported after 9 months of follow-up [39] . However, the laser and B-TURP devices are not always available in different medical centers.…”
Section: Discussionmentioning
confidence: 81%
“…For BPH patients who are at high risk for surgery and/or anesthesia, prostatic artery embolization (PAE) may be a promising technique. No major complications were reported after 9 months of follow-up [39] . However, the laser and B-TURP devices are not always available in different medical centers.…”
Section: Discussionmentioning
confidence: 81%
“…Finally, there were nine articles involving 12 studies eligible for this meta-analysis 614. All of the 12 studies reported the baseline IPSSs, QoL scores, PV, PSA levels, Q max , PVR volume and IIEF-5 scores.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the 24-hour pad test can be performed at a patient's home, we consider it a highly pragmatic and practical measure of secondary prevention, even in settings other than 24-hour in-patient postoperative care. This method could also be widely utilized for evaluation of recently developed treatments in various clinical settings [26,27]. …”
Section: Discussionmentioning
confidence: 99%